Dampak penggunaan media sosial yang tidak bijak bagi kesehatan mental - Ainia, Qurrotul (Maliki Interdisciplinary Journal, 2025)
Using media has become a necessity in today's world. Nonetheless, studies indicate that excessive and careless usage may be detrimental to mental health. People. As a result, social media use has to be restricted. This study aims to determine and examine the effects of careless social media use. for mental well-being and understanding how to manage it The scientific review article approach was employed in the compilation of this research or article, which includes various studies that are relevant to the topic, both those that support and those that contradict it.contradictory using reliable sources, such as scientific journals, previous research, and books. In this study there is a conclusion, namely that the use of social media unwise behavior can cause mental health problems.